Event-Triggered Control for Flapping-Wing Robot Aircraft System Based on High-Gain Observers - Chenxu Xiao; Li Tang; Fei Wang; Sheng You; Hao Xu; Mingchuang Chen; Zhiyuan Lu (Actuators)
In this paper, an event-triggered (ET) control strategy for a flapping-wing robot aircraft system (FWRA) based on high-gain observers is investigated. To solve the vibration problems of bending deformation and torsional deformation that may be encountered in an FWRA during flight, a novel control method is proposed. Firstly, high-gain observers are used to accurately estimate the unmeasured states of the system, and then output feedback ET controllers are designed by combining ET mechanisms. These controllers can effectively suppress the vibrations and ensure the stability of the system, and the occurrence of the Zeno phenomenon is effectively prevented, while the communication burden is reduced. Finally, the simulation results verify the effectiveness of the proposed method.